Master of industrial training 2.0.: Human resources capacity of the project "Professionalitat" - V. V. Dubitsky; A. A. Konovalov; A. I. Lyzhin; A. V Feoktistov; V. S. Neumyvakin (Russian State Vocational Pedagogical University, 2022)
Introduction. The current problems of non-compliance of vocational education with the new technological order and the needs of the digital economy, the demands of society and the current level of technology development actualise the need for changes in vocational education systems in different countries of the world. The connection of such changes with the labour market and the economy as a whole is direct and immediate. Solving education staffing and tackling the professional deficits of teachers of vocational education identified to date has led to the development in the Russian Federation of the Federal project "Professionalitаt" aimed at creating educational and production clusters in the vocational education system, optimising the terms of training in educational programmes and strengthening the state system of teacher training for vocational education in Russia.The aim of the article was to demonstrate and justify the approaches to the implementation of the Federal project "Professionalitаt" in terms of its human resourcing.Methods and research methodology. The study was conducted using the following approaches: a network approach, under which education acts as a system of renewable reflexive social practices inscribed in the system of communication networks (R. Collins, E. Giddens); a practice-oriented approach (D. Warneke, E.-M. Post, A. M. Novikov, D. P. Danilaev); a modular competency-based approach (E. A. Komarnitskaya, P. Pardjono, A. Tapani, A. O. Salonen, W. Wagira); a cognitive approach (R. G. Bolbakov, S. A. Dudko, B. A. Kydyrova, J. B. Feiler, E. E. Schaefer, M. E Stabio).To solve the research questions posed in the current work, the methods of studying and analysing scientific and methodological literature and normative legal documents on the research problem were used. The authors also employed pedagogical forecasting and modelling, and system analysis. The search for theoretical sources was carried out using the scientific resources of the international databases Scopus, Web of Science and the Russian Science Citation Index (eLibrary) with a search depth of 7 years.The theoretical and methodological basis of the study was the theory of the development of professional and vocational pedagogical education and the theory of designing the content of vocational pedagogical education, developed over many years by A. M. Novikov, G. M. Romantsev, O. V. Tarasyuk, V. A. Fedorov, which allowed the authors of the article to develop the possible content of the model of industrial training of a new format. The application of the main provisions of the theories of integration of the content of vocational education (V. M. Kedrov, S. I. Kornev, N. K. Chapaev) was aimed at the formation of soft and polyprofessional competencies required for future professional and pedagogical activities.Results. In the course of the study, the theoretical and methodological substantiation of the original model of the preparation of future masters of industrial training for the organisation of the educational process in the context of the implementation of educational programmes within the framework of the Federal project "Professionalitat" is given. The key (meaningful) component of this model involves the design of competence-oriented content of industrial training provided for the master (Master 2.0), which is revealed through new scientific directions in the fields of neuroeducation, distance learning engineering, Lean-Agile engineering thinking, engineering pedagogy and cognitive science of vocational training. The presented model of the preparation of the master of industrial training of a new formation (Master 2.0.) can be implemented in accordance with the following basic conditions: firstly, the integration of various branches of knowledge in the field of vocational training; secondly, a high-quality level of development of technologies and tools to improve the effectiveness of educational activities in accelerated learning; thirdly, the formation of a cluster that ensures the interaction of educational organisations of the vocational education system with enterprises of the real sector of the economy; fourthly, the creation of a scientific and educational testing ground for the development and testing of innovative content of the master's vocational training 2.0.The scientific novelty of the research consists in the development of a model for the preparation of future masters of industrial training for the organisation of the educational process in the context of the implementation of the programmes of the Federal project "Professionalitat".